Honing Public Speaking Abilities with Effective Speech Training and Practice in SMA YP Unila - Woro Kasih, Elisabeth Ngestirosa Endang; Qodriani, Laila Ulsi; Gulo, Ingatan; Putra, A. Vahry Lilam; Jihantari, Dwi; Fernanto, Hanny Wulandari; Putra, Reza Adha; Putri, Adelia; Zidan, Muhammad; Novendra, Novendra (Universitas Teknokrat Indonesia, 2024)
This article helps High School students become ready for the abilities they’ll need in the future by highlighting the value of public speaking. In order for Senior High School students to succeed in both their personal and professional lives, the essay highlights the significance of public speaking. To that end, this article suggests a community service program that offers training in public speaking, lectures on the subject, and resources for boosting self-confidence. Qualitative methodologies and multiple Google Form questionnaires were used to evaluate the efficacy of this program. Feedback received from SMA YP UNILA students showed enthusiasm and interest in developing their public speaking skills. The results showed a positive impact in showing self-confidence through the ability to communicate well. Through this article, it can be concluded that by developing public speaking skills among high school students, it can prepare them to face the future and become individuals who are better prepared to face the advancement of the era.